SYK Inhibition Induces Apoptosis in Germinal Center-Like B Cells by Modulating the Antiapoptotic Protein Myeloid Cell Leukemia-1, Affecting B-Cell Activation and Antibody Production - Roders, Nathalie; Herr, Florence; Ambroise, Gorbatchev; Thaunat, Olivier; Portier, Alain; Vazquez, Aimé; Durrbach, Antoine (Frontiers in Immunology, 2018)
B cells play a major role in the antibody-mediated rejection (AMR) of solid organ transplants, a major public health concern. The germinal center (GC) is involved in the generation of donor-specific antibody-producing plasma cells and memory B cells, which are often poorly controlled by current treatments. Myeloid cell leukemia-1 (Mcl-1), an anti-apoptotic member of the B-cell lymphoma-2 (Bcl-2) family, is essential for maintenance of the GC reaction and B-cell differentiation. During chronic AMR, tertiary lymphoid structures (TLS) resembling GCs appear in the rejected organ, suggesting local lymphoid neogenesis. We report the infiltration of the kidneys with B cells expressing Mcl-1 in patients with chronic AMR. We modulated GC viability by impairing B-cell receptor (BCR) signaling, by spleen tyrosine kinase (SYK) inhibition. SYK inhibition lowers viability and Mcl-1 protein levels in Burkitt’s lymphoma cell lines. This downregulation of Mcl-1 is coordinated at the transcriptional level, possibly by signal transducer and activator of transcription 3 (STAT3), as shown by (1) the impaired translocation of STAT3 to the nucleus following SYK inhibition, and (2) the lower levels of Mcl-1 transcription upon STAT3 inhibition. Mcl-1 overproduction prevented cells from entering apoptosis following SYK inhibition. In vitro studies with primary tonsillar B cells confirmed that SYK inhibition impaired cell survival and decreased Mcl-1 protein levels. It also impaired B-cell activation and IgG secretion by tonsillar B cells. These findings suggest that the SYK-Mcl-1 pathway could be targeted, to improve graft survival by manipulating the humoral immune response.